Determinants of fiscal effort in sub-Saharan African countries: Does conflict matter? - Okwoche, Princewill U.; Iheonu, Chimere O. (Economics and Business Review, 2021)
This study investigates the determinants of fiscal effort in sub-Saharan African (SSA) within the framework of fiscal reaction functions. Whereas previous studies focusing on SSA have mainly considered the economic non-debt determinants this study accounts for the role of conflict given its persistence in many SSA countries. It employs a variety of panel econometric methods that are applicable in tackling the problem of endogeneity. Specifically the study employs the instrumental variables fixed effects, the two-step generalised method of moments (GMM) and the traditional two-stage least squares techniques. Mainly the evidence shows that although SSA governments have made fiscal adjustments in response to the escalating levels of debt, conflict impacts negatively on this response in SSA. Furthermore, the results affirm the presence of fiscal fatigue in SSA’s fiscal reaction function. Recommendations based on these findings are discussed.